Influence of HfC nanowires on the growth behavior, microstructure and ablation resistance of CVD-HfC coating. Issue 5 (1st April 2019) - Ren, Jincui; Zhang, Yulei; Fu, Yanqin; Zhang, Jian
Abstract: HfC nanowire-toughened HfC ablation resistant coating was prepared on carbon/carbon composites by two steps of chemical vapor deposition. Effects of HfC nanowires on the growth behavior, microstructure and ablation resistance of the HfC coating were researched. Due to the incorporation of HfC nanowires, the deposition rate of the HfC coating was improved, the HfC coating was composed of particle-stacked crystals. After incorporating HfC nanowires, the bonding strength and fracture toughness of the HfC coating increased. HfC nanowires could restrain the crack propagation of HfC coating during ablation, contributing to improving the ablation resistance of HfC coating. After ablation for 60 s, the mass ablation rate of the HfC-coated C/C sample reduced from 0.44 to 0.26 mg/s because of the incorporation of HfC nanowires.